Hypoglycemia, an obstacle to achieving glycemic control. Importance of blood glucose self-monitoring - Inna V. Urlaeva (LLC "MEDIAFORMAT", 2021)
Hypoglycemia is a well-known factor, limiting the patient's ability to achieve adequate glycemic control, and capable of causing a number of car-diovascular diseases (CVDs). Recurrent hypoglycemia may result in severe, potentially fatal complication of diabetes mellitus (DM), the impaired hypoglycemia awareness, raising the risk of severe hypoglycemia up up to six times. Measuring blood glucose levels is a universally accepted com-ponent of glycemic control and one of the strategies for prevention of hypoglycemia, along with the structured patient education in DM manage-ment and the use of modern hypoglycemic medications. Prevention of severe hypoglycemia may be important for prevention of CVDs in patients with DM.